Medication safety practices in healthcare facilities in Kaduna State, Nigeria: a study protocol - Basira Kankia Lawal; Alhaji A. Aliyu; Umar Idris Ibrahim; Bilkisu Bello Maiha; Shafiu Mohammed (SAGE Publishing, 2020)
Background: In recent years, there has been growing concern about patient safety and this is becoming a global problem. Medication safety can be used to describe systematic assessments of healthcare professionals' practices as related to safe use of medicines. Identification and prevention of medication errors is the key component of medication safety. This includes multiple aspects of medication practice and other factors that affect it, such as organisational structure, communication, technologies such as those used for dispensing, and strategies pursued by leadership in cultivating and promoting a culture of safety. Methods: The study adopted a mixed method approach divided into three phases. Phase I is a quantitative phase and involves an assessment of core medication safety practices in the study sites together with an assessment of patient safety culture through the use of the Hospital Survey on Patient Safety Culture (HSOPSC) developed by US Agency for Health Care Research and Quality (AHRQ). Phase II will involve semi-structured interviews with health care providers and focus group discussions with patients to explore their perspectives on medication safety and to explore their experiences concerning medication safety respectively. Phase III will be an intervention study and will utilise the World Health Organisation (WHO) Patient Safety Curriculum Guide: Multi professional edition as the intervention tool. Discussion: The study findings will offer substantial opportunity for improvements. The study will also open up an area of patient safety culture, where not much research has been conducted in Nigeria. Lay summary Exploring medication safety practices in public healthcare facilities in Kaduna State, Nigeria: a study protocol Patient safety is a global problem and there has been growing concern regarding it in recent years. Much less is known about medication safety in Nigeria. We are conducting this study in four public health facilities in Kaduna State, Nigeria in multiple phases that involve multiple stakeholders and data collection methods. In phase Ia, we assessed the presence of basic medication safety practices (such as use of information technology, transition in care practices, and others) by having structured questionnaire based interviews with the Head of Pharmacy department of each of the health facilities. In phase Ib, we are conducting a survey to assess patient safety culture amongst doctors, nurses and pharmacists of the selected health facilities. In phase IIa, we will be conducting one-on-one interviews with healthcare providers to explore their perspectives on medication safety, while phase IIb will involve group discussions with patients to explore their experiences regarding their safety in healthcare. Phase III will be the final phase, which will be an educational intervention phase that will be carried out as a pre- and post-intervention study. We will distribute a questionnaire to participants (pharmacists only), after which we will conduct seminars with the study participants using a patient safety curriculum developed by the World Health Organisation (WHO). Three (3) months later, we will distribute the same pre intervention questionnaire to participants who had responded to the earlier questionnaire and participated in the educational sessions. This study is the first to be conducted in Kaduna State that explores medication safety and patient safety culture. On completion, it will open up an area of patient safety where not much research has been conducted in Nigeria. We expect that the study findings will offer substantial opportunity for making improvements in healthcare safety and quality.